Existence and attractors of solutions for nonlinear parabolic systems - Hamid El Ouardi; Abderrahmane El Hachimi (Electronic Journal of Qualitative Theory of Differential Equations, 2001)
We prove existence and asymptotic behaviour results for weak solutions of a mixed problem (S). We also obtain the existence of the global attractor and the regularity for this attractor in $\left[H^{2}(\Omega )\right] ^{2}$ and we derive estimates of its Haussdorf and fractal dimensions.